Median lethal Dose and Acute Toxicity of Rosa canina L: In-Vivo Study - Zaman Mahmood Jasim; Ghaith Ali Jasim; Ibrahim Saleh Abbas (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
Rosa canina belongs to rosacea family. Rosa. canina has a high concentration of phyto-constituents such as flavonoids, carotenoids, triterpene and vitamins as vitamin C, E, and A Rosa canina have an anti-inflammatory and antioxidant